DEVELOPMENT OF A THROW AND CATCH BALL GAME MODEL FOR THE MANIPULATIVE SKILLS OF CHILDREN AGED 7-9 YEARS - Sta Ayu Salsabila; Qory Jumrotul Aqobah; Ida Zubaida (Universitas Negeri Jakarta, 2025)
Background. The development of manipulative skills such as throwing and catching a ball is a fundamental aspect of motor development in young children, especially those aged 7–9 years. However, many children experience delays in mastering these skills due to a lack of games that are appropriate for their characteristics and needs. Objectives. This study aims to develop an effective ball-throwing and catching game model to enhance manipulative skills in children aged 7–9 years. Method. The method used is Research and Development (R&D) with the ADDIE model approach, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The developed product consists of three game models: Happy Ball, Cheerful Ball, and Joyful Boi. Results. The validation results from physical education experts showed a feasibility rate of 95%, while the validation from early childhood sports practitioners reached 98.61%. Field trials also showed a significant increase in children's manipulative skills and active participation in physical activities. Conclusion. The conclusion of this study is that the developed game models are highly suitable and effective in enhancing children's manipulative skills. The primary contribution of this research is to provide an alternative, enjoyable, contextual, and developmentally appropriate motor learning medium for early childhood.